2019
DOI: 10.3389/fimmu.2019.02751
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Independent Innate Responses to Cytomegalovirus

Abstract: The critical role of interferons (IFNs) in mediating the innate immune response to cytomegalovirus (CMV) infection is well established. However, in recent years the functional importance of the IFN-independent antiviral response has become clearer. IFN-independent, IFN regulatory factor 3 (IRF3)-dependent interferon-stimulated gene (ISG) regulation in the context of CMV infection was first documented 20 years ago. Since then several IFN-independent, IRF3-dependent ISGs have been characterized and found to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 172 publications
(187 reference statements)
3
35
0
Order By: Relevance
“…Moreover, mCherry high and low cells display distinct antiviral gene signatures ( Fig 1D ). While the genes analyzed in this study are designated as interferon-simulated genes (ISGs), IFN-independent upregulation by virus replication of some of these genes has been described [ 22 24 ] and we do not distinguish between virus induced and interferon induced. The putative protective ISGs found in the mCherry low cells at 12 hpi overlap with the genes identified using both ΔHA-mCherry and ΔHA-destabilized GFP at 24 hpi identified previously [ 14 ] ( Fig 1E , top, S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mCherry high and low cells display distinct antiviral gene signatures ( Fig 1D ). While the genes analyzed in this study are designated as interferon-simulated genes (ISGs), IFN-independent upregulation by virus replication of some of these genes has been described [ 22 24 ] and we do not distinguish between virus induced and interferon induced. The putative protective ISGs found in the mCherry low cells at 12 hpi overlap with the genes identified using both ΔHA-mCherry and ΔHA-destabilized GFP at 24 hpi identified previously [ 14 ] ( Fig 1E , top, S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…IFN-independent, IRF-dependent upregulation of some ISGs has been described [ 22 24 ]. In these studies, detection of viral RNA products is still required for virus-induced gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent work by the Mü hlberger lab showed that MARV VP35 inhibits PKR in human but not ERB cells, and there is precedent for IFN-independent response induction by IRF3 or STAT1 of subsets of canonical antiviral genes during in vitro human cytomegalovirus (HCMV) infection. [40][41][42] This does not preclude, however, the alternative possibilities that induction of IFN gene transcription simply occurs at levels too low for nCounter to detect, certain IFN proteins are activated on a post-transcriptional level, and/or the ability of MARV proteins to fully suppress IFN is cell type-dependent, any of which would suggest that IFNs still act as master antiviral response regulators in MARV-infected ERBs, perhaps in a paracrine fashion, without a need for noncanonical explanations. Of most relevance to pathogenesis among the cytokine/chemokine non-DEGs in ERBs is that they appear to be largely pro-or ambi-inflammatory; several are highly induced in primate filoviral infections, including IFNg, IL2, IL4, MIP-1b (CCL4), and CSF2.…”
Section: Article Discussionmentioning
confidence: 99%
“…Unlike other classical components of innate immunity, they are constitutively expressed within the host cells and are generally IFN inducible, thus allowing an immediate response against viral infection through specific targeting of viral/cellular components (Bieniasz, 2003;Hotter and Kirchhoff, 2018). Interestingly, during HCMV infection a subset of classical IFN-stimulated genes (ISGs) may be also induced or upregulated independently of IFN (Ashley et al, 2019).…”
Section: Restriction Factors Vs Hcmv: a Never Ending Fightmentioning
confidence: 99%